Sowing density of four roselle varieties for the dry tropics of the state of Michoacán - Muñoz Flores, Hipólito Jesús; Toledo Aguilar, Rocío; Sáenz Reyes, J. Trinidad; Ruíz Rivas, Magali; Zavala Rangel, Jesús; Barrera Ramírez , Rubén (Revista Mexicana de Ciencias Agrícolas, 2022)
The objective was to evaluate the effect of the yield of four roselle varieties sown in two sowing densities: 8 265 (2) and 13 889 (1) plants ha-1, under conditions of dry tropics in Michoacán. The experimental design was in random complete blocks with a 2 x 4 factorial arrangement, two sowing densities (factor a) and four varieties (factor b), with nine repetitions per treatment. The following variables were recorded: plant height (PHE), diameter at the base of the stem (DBS), number of branches (NB), fresh weight (FW) and dry weight (DW) per plant, and fresh (FRESY) and dry (DRYY) yield per hectare. An Anova (α= 0.05) and a mean comparison test (Tukey, 0.05) were performed to determine the effect of the factors and their interactions (a*b), correlation analysis was also performed between the recorded variables. Significant differences were found within factor a (p≤ 0.05) for the variable PHE, in density 1, PHE was 217 cm and in density 2 it was 197 cm. In factor b, highly significant differences were detected (p≤ 0.05), the Patriota variety reached the highest PHE with 232 cm. No significant differences were identified for the variables DBS, NB and FW, DW, in both factors or their interaction. Regarding the yield of the dry weight of the calyxes, in the factor densities, there were significant differences (p≤ 0.05), density 2 reached the highest DRYY with 573.3 kg ha-1. The variables FW and DW were positively correlated with DRYY (r= 0.82).
Keywords: Hibiscus sabdariffa L.; seasonal agriculture; crop management; productivity